Practice Variations in the Management of Infants With Non–IgE-Mediated Cow's Milk Protein Allergy. Issue 4 (7th July 2022) - Granot, Maya; Machnes Maayan, Diti; Weiss, Batia; Haberman, Yael; Agmon-Levin, Nancy; Shouval, Dror S.
Abstract : Objectives: Infants with non–IgE-mediated food allergies are often referred to gastroenterologists or immunologists. We hypothesized that there are practice variations between these disciplines in the diagnosis and management of such infants. Methods: A computerized questionnaire was distributed between pediatric gastroenterologists and immunologists. The questions addressed diagnosis, management, and follow-up in 3 scenarios of infants with concern for food protein–induced allergic proctocolitis (FPIAP) due to non–IgE-mediated responses to cow's milk. Results: Three cases of infants with suspected FPIAP were presented: milk-based formula-fed (case 1) or breast-fed (case 2) infants that are well appearing and thriving, and a breast-fed infant who is not growing appropriately along with a personal and family history of atopy (case 3). Fifty-eight pediatric gastroenterologists and 32 immunologists completed the questionnaire. Significant differences between gastroenterologists and immunologists were noted regarding the recommended dietary changes in these scenarios. Moreover, despite available guidelines generated by both societies, most physicians confirm the diagnosis based on resolution of symptoms after the dietary change, without re-exposure to the the suspected trigger. In addition, time for recommended re-exposure in infants with FPIAP was also different; most gastroenterologists recommended waiting until 12 months of age, while immunologists suggested reintroduction earlier, up to 6 months of age. Conclusions: We identified significant practice variations in diagnosis and management of FPIAP between pediatric gastroenterologists and immunologists, with lack of adherence to society guidelines. Joint task forces of primary care pediatricians, gastroenterologists, and immunologists should provide uniform guidelines to standardize care.